An archipelago of care Filipino migrants and global networks - McKay, Deirdre (Global research studies, 2016)
"Focusing on the experience of Filipino caregivers in London, some of whom are living and working illegally in their host country, Deirdre McKay considers what migrant workers must do to navigate their way in a global marketplace. She draws on interviews and participant observations, her own long-term fieldwork in communities in the Philippines, and digital ethnography to present an intricate consideration of how these caregivers create stability in potentially precarious living situations. McKay argues that these workers gain resilience from the bonding networks they construct for themselves through social media, faith groups, and community centers. These networks generate an elaborate "archipelago of care" through which migrants create their sense of self"--Provided by publisher.